A randomized controlled trial on the use of Budesonide/formoterol (symbicortr) as an alternative Reliever medication for mild to moderate asthmatic attack in Adult patients in emergency department, hospital universiti Sains malaysia - Kamarudin, Hamizah (2012)
A RANDOMIZED CONTROLLED TRIAL ON THE USE OF BUDESONIDE/FORMOTEROL (SYMBICORT®) AS AN ALTERNATIVE RELIEVER MEDICATION FOR MILD TO MODERATE ASTHMATIC ATTACK IN ADULT PATIENTS IN EMERGENCY DEPARTMENT, HOSPITAL UNFVERSITI SAINS MALAYSIA. Nebulized Salbutamol has been commonly used as the conventional reliever in the treatment of patients with acute exacerbations of asthma regardless of whether in outpatient clinic settings or in the emergency departments. On the other hand, Symbicort turbuhaler is a combination of Formoterol (long acting 02- agonist) and Budesonide (steroid). Salbutamol and Formoterol are 02-agonist that acts as bronchodilators, but Salbutamol is a short acting 02-agonist, whereas Formoterol is a long acting 02-agonist. Budesonide is a steroid that plays a role as an anti-inflammatory agent that usually occur in acute asthma attack. This research is done to evaluate the effectiveness of Symbicort turbuhaler which is a combined long acting 02-agonist and steroid as an alternative reliever in mild to moderate acute axacerbation of bronchial asthma and to look at patient’s acceptance regarding the use of Symbicort turbuhaler and the feasibility in starting Symbicort maintanance and reliever therapy (SMART) in emergency department. To evaluate the effectiveness of Symbicort therapy as an alternative reliever in treating mild to moderate acute exacerbation of bronchial asthma. To evaluate control of asthma based on Asthma Control Test (ACT) among adult asthmatic patients that presented to emergency department HUSM. To evaluate the effectiveness of Symbicort turbuhaler as an alternative treatment for mild to moderate asthma exacerbation by using respiratory rate, oxygen saturation and peak expiratory flow rate (PEFR) as objective assessment tools for the severity of asthmatic attack and patient’s response to treatment. To evaluate the effectiveness of symbicort turbuhaler as an alternative treatment for mild to moderate asthma exacerbation by using Visual Analog Score (VAS) and 5-point Likert Scale of breathlessness as subjective assessment tools for the severity of asthmatic attack and patient’s response to treatment. To understand patient’s acceptance regarding the use of Symbicort turbuhaler as an acute asthma reliever and maintainance therapy (SMART). To evaluate the fraction exhaled nitric oxide (FENO) level in asthmatic patient and its association with asthma control. A randomized controlled trial was done from March until August 2011 between nebulizer Salbutamol and Symbicort turbuhaler in adult patients with mild to moderate acute exacerbation of bronchial asthma who presented to Emergency Department HUSM. Patients who fulfilled the criteria and agreed to participate in this study were randomly assigned either nebulizer Salbutamol or Symbicort turbuhaler as the treatment. Objective and clinical parameters such as respiratory rate (RR), oxygen saturation (SPO2), peak expiratory flow rate (PEFR) and fraction of exhale nitric oxide (FENO) were recorded before and after treatment. Parameters were analyzed using SPSS version 18.0. A total of 32 patients fulfilled the inclusion criteria and consented to participate in this study. After randomization, 17 patients were chosen to receive nebulized salbutamol and another 15 patients received symbicort turbuhaler. There were significant improvements in respiratory rate (RR), oxygen saturation (SPO2) and PEFR in patients received symbicort turbuhler (p=0.001, p=0.027 and p=<0.001 respectively). This result is as significant as patients received nebulized salbutamol. When comparing the means difference between this two groups using ‘Independence ttest’, it showed that there were no significant difference in terms of changes in respiratory rate, SPO2 and PEFR (p=0.687,p=0.350 and p=0.507 respectively). In terms of subjective parameters using ‘Visual Analog Score’ and ‘5-point Likert Scale’ of breathlessness, it also showed that there were no significant difference in patients who received symbicort turbuhaler or nebulized salbutamol (p=0.765 and p=0.688 respectively). Regarding asthma control based on Asthma Control Test (ACT) score, by using Me Nemar test, there were no significant difference in asthma control in patients started on SMART therapy or with MDI salbutamol plus MDI budesonide (p=0.754). We also found that SMART therapy were well accepted by most of the patients based on questionnaires answered. From this randomized controlled trial study, it showed that symbicort turbuhaler can be used as an alternative treatment for patients with mild to moderate exacerbation of asthma as there were no significant difference improvements in objective parameters and in subjective parameters compared to nebulized salbutamol.